Grit and success: a brief outlook / Azfahanee Zakaria and Syed Mohammed Alhady - Zakaria, Azfahanee; Alhady, Syed Mohammed (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2021)
Grit allows a person to get through challenges which he or she faces in obtaining and reaching certain goals. When a person has grit, he or she will be willing to invest time, energy and ready to give up many other things as a mean achieve the goals. Gritty people are said to have high commitments which ensures their track to the plans. Gritty people do not give up and they always sustain the stamina to move on consistently. They will find ways and alternative to reach their goals (Weir, 2020).